Analisis Budaya Perusahaan dan Work Life Balance melalui Motivation Work Behavior terhadap Kinerja Karyawan pada CV. Duta Jaya Makmur - Andriani, Dewi (Jurnal Ilmiah Manajemen, Bisnis dan Kewirausahaan, 2026)
This study aims to analyze the influence of organizational culture, work-life balance, and job satisfaction on employee performance through work motivation as an intervening variable at UD. Duta Jaya Makmur. The method used was quantitative with an explanatory research approach, using primary data from the distribution of questionnaires and field observations to 100 employees of the company. Data analysis was carried out with the help of SmartPLS4 which showed that organizational culture and work-life balance have a positive and significant influence on work motivation and employee performance. Work motivation has also been shown to play a key role in strengthening the influence of these variables on employee performance. The results of the study confirm that a strong organizational culture and good work-life balance management can improve employee motivation and work performance in a sustainable manner.